Structure and molecular dynamics of perovskite N(CH3)4MnCl3 crystals of high-temperature phases I and (I′) - Moon Young Choi; Ae Ran Lim (Scientific Reports)
Abstract New developments in perovskite-type N(CH3)4MnCl3 single crystals were examined, with a focus on their high-temperature phases. The phase transition temperature (TC) was established as being 390 K via differential scanning calorimetry and powder X-ray diffraction analyses. At 300 K, the single-crystal structure has hexagonal symmetry and exhibits thermal stability up to a high temperature of approximately 680 K. Additionally, 1H and 13C nuclear magnetic resonance (NMR) chemical shifts displayed continuous changes with temperature, without any anomalous behavior observed near TC. The 1H spin–lattice relaxation time, which represents the molecular motion of 1H, shows slight changes near TC. The phase transition from phase I to I (′), associated with changes in the rotational degrees of freedom of N(CH3)4 + molecules, is considered second-order. The small change between phases I and I (′) is consistent with a change in the space group in the same hexagonal structure previously reported. These physical properties indicate the potential applications of N(CH3)4MnCl3 as an organic–inorganic hybrid perovskite material.